Fiscalização de contratos de terceirização de mão de obra na Universidade Federal de Sergipe: uma análise sobre a atuação e percepção dos agentes envolvidos no processo - Conceição, Sérgio Sávio Ferreira da (2019)
Routinely, when it comes to outsourcing services, it is common to think that the public interest is properly achieved with the consequent hiring of the provider, through a bidding process. However, the execution of the contract, in accordance with that agreed upon, is possibly the most critical phase of the whole process, since it is through this activity that the achievement of all previously planned objectives will be guaranteed. In order for this crucial phase to be carried out as efficiently as possible, it is advisable for management to appoint managers and prosecutors for trained contracts, enabling them to function as guarantors of the best execution of the object. In this context, the objective of this study is to investigate the perception of the participating agents (managers, prosecutors and prepossessors) on the process of supervision of outsourcing contracts at the Federal University of Sergipe. The theoretical approach is based on the concepts of the outsourcing process, focusing on public administration, as well as on administrative contracts and their characteristics, and on contract management and supervision, focused on the performance and responsibilities of the prosecutors. To achieve this objective, a qualitative study was carried out, with a descriptive approach, adopting the single case study as a research strategy. Data were collected through semi-structured interviews (with manager, tax and prepositions), documentary research and direct observations, and later submitted to content analysis in order to group the answers by the proposed categories and elements of analysis. The analysis of the data allowed to situate the participants' perception of the process, allowing them to identify their greatest difficulties, fears, how they feel performing their function and, above all, what are their suggestions for improving the practice based on what they observe and live together day by day. It is concluded, therefore, that there are satisfactory conditions for the execution of the activities by the agents, based on the analysis of the responses to the proposed elements, either within the scope of what is available, working conditions, or in the conditions necessary for the assignments. In addition, with regard to perception, it was possible to verify that there is a good perception on the part of the respondents about their role in the process, that is, there is a satisfactory understanding of what is expected of each one, compared to what is actually executed.